IMPLEMENTASI PROGRAM CERDAS ISTIMEWA DAN BAKAT ISTIMEWA (CIBI) DALAM PENGEMBANGAN PRESTASI AKADEMIK DAN NON AKADEMIK DI SD MUHAMMADIYAH CONDONGCATUR - Tri Mardiah; Nurul Hidayati Rofiah (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
This study aims to answer: 1) the implementation of the CIBI program in developing academic and non-academic achievements at SD Muhammadiyah Condongcatur, 2) supporting and inhibiting factors for the implementation of the CIBI program in developing academic and non-academic achievements at SD Muhammadiyah Condongcatur.This type of research uses descriptive qualitative research. The subject of this study was a team of coordinators and students who participated in the CIBI program. Data collection techniques use triangulation techniques and sources. The data analysis technique uses interactive data models of Miles and Huberman.The results of the study are as follows: 1) Implementation of the CIBI program in developing academic and non-academic achievements at SD Muhammadiyah Condongcatur through 3 stages, namely the planning, implementation, and evaluation stages. Planning for the CIBI program includes determining objectives, stages of the program, preparation of teaching staff, student selection criteria, facilities and infrastructure, and program funding. The implementation of the CIBI program includes the learning process, time and schedule of implementation, teaching materials, learning materials, and learning methods. The evaluation of the CIBI program put forward the cognitive and psychomotor aspects of students, the preparation of instruments for the assessment of the CIBI program, and the follow-up of the CIBI program. 2) Supporting factors of the CIBI program in developing academic and non-academic student achievements include: there is a coordinating team that teaches in the CIBI program in accordance with their fields, the CIBI program facilities are very complete, and school funding supports. The inhibiting factor of the CI program in developing academic achievement is the lack of time and teaching staff, scheduling material distribution is very difficult to do, and the difficulty of how to give motivation is always stable. While the inhibiting factors of the BI program in developing non-academic achievements are weather conditions and students who take part in 2 activities outside of school.